Numerical Modeling of Gamma-Ray Burst Spectra - Lartsev, A. I.; Lukin, V. V. (Lobachevskii journal of mathematics, 2025)
The model of gamma-ray burst (GRB) from magnetorotational supernova after its explosion is proposed in order to investigate burst gamma radiation spectrum. Formation and radiative acceleration of the collimated jet inside the channel in the Compton plasma cloud formed around the metallic core is considered. The observed spectrum is proposed to be the result of rising from the star and cloud photons scattering during the relativistic stream acceleration. These phenomena are described by a three-dimensional model of relativistic radiative hydrodynamics including the full radiative transfer equation with scattering integral. Due to relativistic speed of the flow one need to use a Compton scattering model that takes into account the change in photon frequency when colliding with fast-moving electrons. To obtain numerical solution of the radiation gas dynamics equations the splitting method is used. For the radiative transfer equation with scattering the short characteristics method is used, and for the relativistic hydrodynamics the Godunov-type one. The algorithm is designed for tetrahedral meshes and adapted for computations on cluster systems with graphics processing units. The central object radiation pressure accelerated the matter up to 90 of the light speed and the observed spectrum shifted from black-body radiation to the X-ray range. The spectra for observator different points of view are calculated.